2006
DOI: 10.1191/0961203306lu2324oa
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies to dsDNA: An Overview of Laboratory Assays

Abstract: This brief review is focused on different methodologies available for detection of anti-dsDNA antibodies with respect to the best adequacy between biological results of laboratory and clinical significance. A large array of assays has been developed for the measurement of anti-dsDNA. New assays continually introduced have reflected not only technical innovations to avoid difficulties of some assays, but even more with hope to correlate better with systemic lupus erythematosus (SLE), particularly with its clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
1
25
0
3
Order By: Relevance
“…It has been suggested that low-affinity anti-DNA antibodies (as detected by ELISA) in autoimmune mice might be less pathogenic compared to specific Crithidia luciliae-positive high-affinity antibodies. However, to our knowledge this hypothesis has not been circumstantiated experimentally (Hamilton et al, 2006;Rouquette and Desgruelles, 2006).…”
Section: Anti-dna Autoantibody Detection In Micementioning
confidence: 61%
See 1 more Smart Citation
“…It has been suggested that low-affinity anti-DNA antibodies (as detected by ELISA) in autoimmune mice might be less pathogenic compared to specific Crithidia luciliae-positive high-affinity antibodies. However, to our knowledge this hypothesis has not been circumstantiated experimentally (Hamilton et al, 2006;Rouquette and Desgruelles, 2006).…”
Section: Anti-dna Autoantibody Detection In Micementioning
confidence: 61%
“…This was called the ''two-receptor paradigm'' of TLR-mediated cellular activation (Lau et al, 2005). The idea became popular because it explained how usually inert DNA could provoke an immune response in SLE (Rouquette and Desgruelles, 2006), namely by activation of the BCR and by TLR9 engagement. However, autoimmune models that did not employ repertoire-restricted immunoglobulin-transgenic mice do not show a predicted inhibition of anti-DNA autoantibody production or SLE symptom amelioration through deletion of TLR9 in vivo (Lartigue et al, 2006;Wu and Peng, 2006;Yu et al, 2006).…”
Section: The Two-receptor Paradigmmentioning
confidence: 99%
“…Néanmoins, les techniques évoluent avec, en particulier, des modifications dans le DNA choisi comme antigène, l'optimisation des procédures de coating et la capacité de détecter essentiellement des anti-DNA d'affinité forte ou intermédiaire [10].…”
Section: Discussion Et Conclusionunclassified
“…Plusieurs tests existent, basés sur des technologies différentes : immunofluorescence indirecte sur Crithidia luciliae (CLIF), radio-immunologie (test de Farr) et tests Elisa dont l'utilisation est en progression [9,10,12]. Si tous ces tests sont aptes à doser les anticorps anti-DNA natif, il existe des discordances entre eux dans les résultats liées en partie aux principes méthodologiques et à un moindre degré au recrutement des patients testés [11,21].…”
Section: Introductionunclassified
“…Different combinations of these methods are used in diagnostic laboratories worldwide, without a consensus on exclusive methods (8,10). An important cause of discrepancies between results obtained with different methods lies in the avidity of antibodies.…”
mentioning
confidence: 99%